Reassessing Christopher Alexander’s theory of urban morphogenesis - Michael W. Mehaffy; Bin Jiang (Computational Urban Science)
Abstract The architect Christopher Alexander made major contributions in architecture, city science, computer science and other fields. His earlier works, notably “A City is Not a Tree,” contributed to the understanding of cities as complex adaptive systems. Less well known, although no less theoretically ambitious, was Alexander’s later work after the year 2000. Here we explore the potential contribution of this work to contemporary urban challenges, focusing on Alexander’s magnum opus The Nature of Order: An Essay of the Art of Building and the Nature of the Universe. We assess its theoretical contribution to the field of sustainable urbanism, with a focus on its computational aspects, as well as the critique it poses for conventional approaches to urban sustainability.